1998
DOI: 10.1002/(sici)1096-8628(19980106)75:1<22::aid-ajmg6>3.0.co;2-s
|View full text |Cite
|
Sign up to set email alerts
|

Excess of mild errors of morphogenesis in childhood lymphoblastic leukemia

Abstract: The prevalence of 55 well-defined mild errors of morphogenesis (MEMs) was determined in 100 children with acute lymphoblastic leukemia (ALL), their 80 sibs, 91 mothers, and 76 fathers. Seventy-four patients were treated in Pécs (Hungary) and 26 in Tübingen (Germany). Only white Caucasian index cases were included in the study. Two-hundred children examined for acute infections served as controls. In addition, we analyzed the family history for birth defects and malignancies, associated major malformations, bir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Until now, seven earlier studies were performed describing the prevalence of minor physical anomalies in pediatric cancer patients [Kobayashi et al, 1968; Stojimirovic, 1981; Méhes et al, 1985, 1994, 1998; Fekete et al, 1987; Roganovic et al, 2002]. Méhes et al [1985] was able to examine 106 pediatric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, seven earlier studies were performed describing the prevalence of minor physical anomalies in pediatric cancer patients [Kobayashi et al, 1968; Stojimirovic, 1981; Méhes et al, 1985, 1994, 1998; Fekete et al, 1987; Roganovic et al, 2002]. Méhes et al [1985] was able to examine 106 pediatric cancer patients.…”
Section: Discussionmentioning
confidence: 99%
“…We had no special control group in this study. However, when investigating the prevalence of mild errors of morphogenesis in childhood malignancies in earlier studies [Méhes et al, 1985, 1998], no supernumerary digital creases were found in 204 children with leukemia or soft tissue tumors, in their 408 first‐degree relatives, and in 204 healthy control subjects.…”
Section: To the Editormentioning
confidence: 99%
“…The reliance on major malformations ignores the fact that many syndromes primarily manifest minor anomalies, which can be true even for Down syndrome [Preus, 1977]. There are a limited number of studies of the prevalence of minor physical anomalies in childhood cancer patients [Kobayashi et al, 1968; Stojimirovic, 1981; Méhes et al, 1985, 1998; Fekete et al, 1987; Roganovic et al, 2002]. In all of these studies, the prevalence of minor anomalies was increased.…”
Section: Introductionmentioning
confidence: 99%